"BOXING DAY" IN ENGLISH FOOTBALL (Physical Culture and Sport: Scientific Perspective, 2024)
Analyzing the existing studies in football, we did not find any related to the clarification of the role of "Boxing Day" within the framework of holding one of the best football championships in the world. Purpose: to find out the advantages and disadvantages of "Boxing Day" in English football. Methods: analysis and synthesis, comparison and generalization. Results: Achieving high results in football depends not only on the level of preparation of the players (technical, tactical, physical, mental and theoretical) but also on a number of circumstances, in particular: the venue, the calendar and schedule of competitions, the quantitative and qualitative composition of the club, which in turn become are one of the key components of the team's success. This is especially true for championships where the level of clubs is not significantly different from each other (for example: "APL" - England, "La Liga" - Spain, "Bundesliga" - Germany, "Seria A" - Italy; "Ligue 1" - France and etc.). In order to win such competitions, it is necessary to demonstrate the highest level of play throughout the season (9-10 months), which is extremely difficult (taking into account the parallel holding of international club matches and national team matches). Such a phenomenon as "Boxing Day", when teams have to play several matches in the shortest period of time (basically 3 games in 6-7 days) can make adjustments to the distribution of seats at the end of the season. Conclusion: On the one hand, the difficult pre-New Year's schedule (from the end of December to the beginning of January) in the "EPL" is dangerous: excessive physical load on athletes; lack of effective recovery of players; high risk of injury to football players, etc. On the other hand, the leaders of the English "Premier League" consider it inappropriate to refuse this event because it is generally: a holiday for a large number of fans; an important event for broadcasters and a significant source of income that keeps professional football clubs alive.
Keywords: "Boxing Day"; English football; "EPL"; professional clubs; spectacle